Performance of Carbon Fiber Filament Reinforcing Cement Mortar - El-Sayed Salama, Ahmed Hamed; Edris, Walid Fouad (Civil Engineering Journal, 2021)
This paper aims to study the effect of Carbon Fiber Filament (CFF) with different ratios and lengths on the physical and mechanical properties of cement mortar. An experimental program included 3 cm fixed length of CFF with 0, 0.25, 0.5, 0.75, and 1% different ratios by weight of cement addition were used in cement mortar cubes. Another experimental program of 0.5% CFF ratio with 1, 2, 3, 4, and 5 cm different lengths by weight of cement addition was used in cement mortar prisms. The physical and mechanical properties of cement mortar containing CFF were experimentally investigated at 7 and 28 days of curing. Workability, by means of flow table test, were measured. Density is conducted for cubes and prisms at the age of 28 days. At ages of 7 and 28 days, compressive and flexural strengths were studied. The study showed a reduction in workability with the increase of CFF ratios and lengths by 0.0 to 2.7% and by 0.9 to 5.4% respectively. Moreover, an improvement in density, compressive, and flexural strengths was observed. At ages of 7 and 28 days, the results showed that compressive strength increased by 33 and 31% respectively at 0.5% of CFF ratio while the flexural strength increased by 125 and 327% respectively with CFF length of 5 cm.Â Doi: 10.28991/cej-2021-03091753 Full Text: PDF